Structure-based screening of inhibitor platelet-derived growth factor from ethanol extract of Uncaria gambir (Hunter) Roxb. as an antifibrotic in keloid fibroblast cells - Sri Widia A. Jusman,, Maftuhatun Fista Amalia, Reni Paramita,, Sri Ningsih, Fadilah Fadilah (Journal of Applied Pharmaceutical Science, 2023)
This study aimed to determine the potency of the compounds in gambir [Uncaria gambir (Hunter) Roxb.] to inhibit the proliferation of keloid fibroblasts using an in silico study with molecular docking and an in vitro assay. In this study, the interaction between compounds found in the gambir plant and platelet-derived growth factor subunit A (PDGF-α) as the target protein and the percentage inhibition were analyzed to determine its potential as a candidate for herbal-based keloid therapy. The compounds found in the plant gambir [(+)-catechin, gambirin A1, gambirin A2, gambirin B1, gambirin B2, gambirin C, procyanidin B1, procyanidin B2, epigallocatechin gallate, and (+)-epicatechin] were docked to the target protein PDGF-α (PBD ID: 3MJK). An MTT assay was conducted to determine the cytotoxicity of each compound. The three compounds gambirin A1, procyanidin B2, and neooxygambirtannine had the best affinity values of −12.8324, −13.4987, and −14.5446 and PKI values of 8.962, 10.218, and 9.129, respectively. The IC50 of the ethanolic extract of gambir was 22.40 ± 0.071 ug/ml against keloid fibroblast cells. The potential bioactive compounds as PDGF inhibitors have been identified, namely, gambirin A1, procyanidin B2, and neooxygambirtannine. These compounds can be isolated for further research. IC50 can be used to understand the molecular mechanism of the inhibition of the gambir extract against keloid fibroblast cells.